Stanisława Niemcówna i Józefa Berggruen – propagatorki krajoznawstwa wśród młodzieży krakowskiej okresu międzywojennego - Dormus, Katarzyna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2021)
Local lore – a comprehensive study of everything pertaining to a given country – started to develop in Poland in the 18th century and this development accelerated in the 19th century. Throughout the partition period, local lore contributed to the strengthening of Polishness and the popularization of knowledge about the country. During the Second Polish Republic, local lore transformed into a social movement, with Cracow at its center. Youth organizations focused on local lore began to form next to the Cracow chapter of the Polish Sightseeing Society. Teachers were particularly well suited to organize and lead the local lore movement. Stanisława Niemcówna and Józefa Berggruen from the 10th Public Female Gymnasium in Cracow were two examples of such teachers. They led the local lore society at their school and took on additional leadership roles in the wider movement, pioneering local lore and promoting new teaching methods.
Keywords: Stanislawa Niemcówna; Józefa Berggruen; Cracow (Poland; region); local lore; geography